Assessment And Construction Of Norms For Agility Among College Students Of Kashmir Region - Waseem Raja Malik ,Sonam Gytso , C. Saravana Gandhi (Elementary Education Online, 2021)
The purpose of the study was to compare and construct norms for agility among undergraduate male college students of Kashmir region of union territory of Jammu and Kashmir. To achieve the purpose 2412 under graduate male college students of age group 19 to 21 years from different colleges in different districts of north, central and south divisions of Kashmir region were randomly selected as subjects. Agility was selected as criterion variable and was measured by 4 × 10 meters shuttle run. The collected data was analyzed by using analysis of variance (ANOVA) and if obtained ‘F’ ratio was found to be significant; Scheff’s post hoc test was applied to know the paired mean difference. The level of significance was fixed at 0.05. To construct norms, Hull scale value of respected classes was continuously added and subtracted from the respective means for determining the values from zero to hundred in the scale. The scores were further classified in to five grades I.e. excellent, good, average, poor and very poor. The results of this study indicate that male college students of north, central and south divisions of Kashmir region significantly differ on agility. Also, the results of the study revealed that irrespective of age and division maximum number of male college students falls in the category of average. Those who score below the 50th deciles on agility in their respective age group should be encouraged to improve their agility. National level special fitness programme will be designed and implemented to the poor fitness students.